Characterization and simulation studies on the corrosion products of HR230 and 740 H alloys in CO2 with 7% H2O environment at 1000 ℃. (15th April 2023) - Guo, Tingshan; Liang, Zhiyuan; Zhao, Qinxin
Abstract: The corrosion behavior of HR230 and 740 H alloys in CO2 with 7% H2 O environment at 1000 ℃ were investigated. Some TiO2 oxides and Al2 O3 internal oxides were observed on the surface and in the matrix of 740 alloy respectively, which caused the weight gain of 740 H alloy was higher than that of HR230 alloy. The chemical adsorption capacity of H2 O molecules on the surfaces of both alloys was stronger than that of CO2 molecules. The H2 O molecule preferentially reacted with both alloys to form a Cr2 O3 oxide layer, while the delayed CO2 molecule caused the internal oxidation of Al. Highlights: The corrosion behavior of HR230 and 740 H alloys in CO2 with 7% H2 O at 1000 ℃ were investigated. TiO2 oxides and Al2 O3 internal oxides were formed on the surface and in the matrix of 740 alloy respectively. The volatile CrO2 (OH)2 oxides were formed on the surface of Cr2 O3 oxide layer. The adsorption capacity of H2 O molecules on the surfaces of both alloys was stronger than that of CO2 molecules. The internal oxidation behavior of Al was mainly caused by CO2 molecules.